By Reef and Palm - Becke, Louis, 1855-1913 (Salt Lake City, UT : Project Gutenberg, 2003)
"By Reef and Palm" by Louis Becke is a collection of short stories written during the late 19th century, likely in the context of Becke's own experiences in the South Pacific islands. The stories explore themes of adventure, trade, and human relationships in the setting of Polynesia, often weaving the complexities and realities of island life with elements of romance and conflict. The opening of the book introduces readers to the author's background and experiences, highlighting his arrival in Samoa and detailing the vibrant and tumultuous atmosphere of the time. It offers glimpses into various characters, including traders, native islanders, and their intricate relationships, as well as the adventures that Becke encounters, suggesting a rich tapestry of narratives that reveal both the beauty and harshness of island life. The introduction sets the stage for the subsequent stories, encompassing various aspects of life in the Pacific, from love and betrayal to survival and culture. (This is an automatically generated summary.)
Challis the doubter -- 'Tis in the blood -- The revenge of Macy O'Shea -- The rangers of the Tia Kau -- Pallou's Taloi -- A basket of bread-fruit -- Enderby's courtship -- Long Charley's good little wife -- The methodical Mr. Burr of Maduro -- A truly great man -- The doctor's wife -- The fate of the Alida -- The Chilean bluejacket -- Brantley Of Vahitahi.
Release date is 2003-03-01
Produced by Col Choat. HTML version by Al Haines.
Keywords: Short stories; Adventure stories, Australian; Pacific Area -- Social life and customs -- Fiction; Oceania -- Fiction